MANAJEMEN REPLANTING KELAPA SAWIT (ELAEIS GUINEENSIS JACQ) PETANI SWADAYA KECAMATAN MELIAU KABUPATEN SANGGAU - Jitro Rian Atria; Maswadi; Wanti Fitrianti (PT. Hasba Edukasi Mandiri, 2025)
Indonesia is the largest producer of palm oil in the world, with a significant increase in plantation area, yet faces the challenge of increasing old and damaged plants affecting productivity. To address this, oil palm replanting is necessary, with government support to ensure the sustainability and productivity of independent smallholder plantations. The purpose of this study is to understand the management of oil palm replanting by independent farmers in Meliau District, Sanggau Regency. This research, which uses a qualitative descriptive method and utilizes both primary and secondary data, involves a sample of 40 respondents who are independent farmers. The results show that the replanting process in Sungai Kembayau Village using the mass clearing method demonstrates a strong commitment to long-term productivity improvement of the plantations. However, there are deviations from standard operating procedures that can affect the efficiency and outcomes of replanting, such as variability in chipping thickness, neglect of cover crop use, and inconsistencies in pest control dosing.